Solve for x (complex solution)
x=-4+8\sqrt{2}i\approx -4+11.313708499i
x=-8\sqrt{2}i-4\approx -4-11.313708499i
Graph
Share
Copied to clipboard
-2x^{2}-16x=288
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
-2x^{2}-16x-288=288-288
Subtract 288 from both sides of the equation.
-2x^{2}-16x-288=0
Subtracting 288 from itself leaves 0.
x=\frac{-\left(-16\right)±\sqrt{\left(-16\right)^{2}-4\left(-2\right)\left(-288\right)}}{2\left(-2\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -2 for a, -16 for b, and -288 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-16\right)±\sqrt{256-4\left(-2\right)\left(-288\right)}}{2\left(-2\right)}
Square -16.
x=\frac{-\left(-16\right)±\sqrt{256+8\left(-288\right)}}{2\left(-2\right)}
Multiply -4 times -2.
x=\frac{-\left(-16\right)±\sqrt{256-2304}}{2\left(-2\right)}
Multiply 8 times -288.
x=\frac{-\left(-16\right)±\sqrt{-2048}}{2\left(-2\right)}
Add 256 to -2304.
x=\frac{-\left(-16\right)±32\sqrt{2}i}{2\left(-2\right)}
Take the square root of -2048.
x=\frac{16±32\sqrt{2}i}{2\left(-2\right)}
The opposite of -16 is 16.
x=\frac{16±32\sqrt{2}i}{-4}
Multiply 2 times -2.
x=\frac{16+32\sqrt{2}i}{-4}
Now solve the equation x=\frac{16±32\sqrt{2}i}{-4} when ± is plus. Add 16 to 32i\sqrt{2}.
x=-8\sqrt{2}i-4
Divide 16+32i\sqrt{2} by -4.
x=\frac{-32\sqrt{2}i+16}{-4}
Now solve the equation x=\frac{16±32\sqrt{2}i}{-4} when ± is minus. Subtract 32i\sqrt{2} from 16.
x=-4+8\sqrt{2}i
Divide 16-32i\sqrt{2} by -4.
x=-8\sqrt{2}i-4 x=-4+8\sqrt{2}i
The equation is now solved.
-2x^{2}-16x=288
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{-2x^{2}-16x}{-2}=\frac{288}{-2}
Divide both sides by -2.
x^{2}+\left(-\frac{16}{-2}\right)x=\frac{288}{-2}
Dividing by -2 undoes the multiplication by -2.
x^{2}+8x=\frac{288}{-2}
Divide -16 by -2.
x^{2}+8x=-144
Divide 288 by -2.
x^{2}+8x+4^{2}=-144+4^{2}
Divide 8, the coefficient of the x term, by 2 to get 4. Then add the square of 4 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+8x+16=-144+16
Square 4.
x^{2}+8x+16=-128
Add -144 to 16.
\left(x+4\right)^{2}=-128
Factor x^{2}+8x+16. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+4\right)^{2}}=\sqrt{-128}
Take the square root of both sides of the equation.
x+4=8\sqrt{2}i x+4=-8\sqrt{2}i
Simplify.
x=-4+2\times 2^{\frac{5}{2}}i x=-2\times 2^{\frac{5}{2}}i-4
Subtract 4 from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}